The Role of Internal Audit Practice in Promoting Operational Compliance: Evidence from Addis Ababa Housing Development Corporation - Gizachew Melisew, Chekol (Syntax Literate, 2024)
This research investigates the role of internal audit practices in promoting operational compliance within public sector organizations, with a focus on Addis Ababa Housing Development Corporation. Internal audit is essential in ensuring compliance with policies, laws, and regulations, contributing to the overall effectiveness and governance of organizations. The study examines key internal audit practices such as audit frequency, auditor independence, auditor competency, and audit reporting. A quantitative approach was employed, utilizing structured questionnaires distributed to finance managers, internal auditors, and senior accountants. Data were analyzed using descriptive and inferential statistics to determine the impact of internal audit practices on operational compliance. he results show that all the studied audit factors positively contribute to enhancing compliance. Auditor independence had the most significant influence, followed by auditor competency, audit frequency, and audit reporting. This highlights the necessity of frequent audits, unbiased auditor reporting, and specialized skills to ensure adherence to operational regulations. These findings emphasize the importance of strengthening internal audit practices in Ethiopia's public sector to improve governance and mitigate organizational risks. The study provides insights into improving audit practices, especially in resource-constrained environments like Ethiopia, and underscores the need for continued investment in auditor training and independent reporting mechanisms to safeguard organizational integrity